PSEG and the promise of wind power. Issue 1 (17th December 2019) - Rosenberg, Stuart
Abstract : Theoretical basis: The following theoretical concepts are applicable to the case and its learning objectives: Stakeholder Power-Interest Matrix and Carroll's Pyramid of Corporate Social Responsibility. Research methodology: Information was obtained in three separate interviews with PSEG. In February 2018, an introductory phone conference was conducted with a number of senior managers within PSEG, including the Director of Development and Strategic Issues, Kate Gerlach. In April 2018, an onsite interview was conducted with Gerlach, who connected the author with Scott Jennings. A phone interview was conducted with Scott Jennings in May 2018 and follow-up communication with him was handled via e-mail. The information obtained from these interviews was supplemented by material obtained from secondary sources. None of the information in the case has been disguised. Case overview/synopsis: Scott Jennings, a Vice President at PSEG, the diversified New Jersey-based energy company, was the project leader for a large commercial wind farm that was to be built off the coast. The project, Garden State Offshore Energy, a joint venture between PSEG and Deepwater Wind, an experienced developer of offshore wind projects, had been announced over six years earlier, in late 2008. In the time that had passed, the Garden State Offshore Energy project team had waited for the New Jersey Bureau of Public Utilities, which had been tasked by Governor Chris Christie to evaluate the project costs before it could authorize the actual construction of the wind turbines. Justifying the project on a cost basis proved to be difficult; despite the growing public sentiment in favor of projects that utilized renewable energy sources such as wind power, the Garden State Offshore Energy team was unable to move the project forward. Scott needed to decide whether it made sense to continue to hold regular meetings with the Garden State Offshore Energy team. Scott's colleagues suggested that Scott speak with senior management at PSEG to find out if the resources that had been dedicated to the Garden State Offshore Energy project could be shifted to other projects that might be more feasible. Complexity academic level: This case is suitable for courses in Sustainability. It is appropriate to use the case in undergraduate courses to illustrate decision making in a regulated industry. Sufficient information is presented in the case to debate both sides of the offshore wind authorization issue.